2017
DOI: 10.1111/are.13405
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fishmeal levels affect the volatile compounds in cooked muscle of farmed large yellow croaker Larimichthys crocea

Abstract: A comparative study on the volatile compounds in cooked muscle of wild and farmed large yellow croaker (LYC) was conducted. The two farmed LYC groups were fed with diets containing 44% (CF) and 25% (LF) of fish meal (FM) respectively. Results showed that 48 volatiles, including aldehydes, alcohols, ketones, hydrocarbons, aromatics, acids, esters, furans and miscellaneous compound, were detected in cooked fillets. The LF group had significantly lower amounts of total aldehydes and ketones, higher content of mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…The volatile flavour components in fish oil mainly comprise aldehydes, alcohols, ketones, acids, and alkanes (Mu et al ., 2017). As previously reported, aldehydes are mainly derived from oxidative degradation of UFAs, and their sensory thresholds are generally very low, which greatly contributes to the overall flavour, and directly affect the flavour of fish oil (Liu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile flavour components in fish oil mainly comprise aldehydes, alcohols, ketones, acids, and alkanes (Mu et al ., 2017). As previously reported, aldehydes are mainly derived from oxidative degradation of UFAs, and their sensory thresholds are generally very low, which greatly contributes to the overall flavour, and directly affect the flavour of fish oil (Liu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Unsaturated bonds in oil are destroyed to form peroxides, which are decomposed into many toxic substances in turn (Endo, 2016). The higher content of unsaturated fatty acids (UFAs) makes the quality of aquatic products more vulnerable to lipid changes (Honold et al ., 2016; Mu et al ., 2017). Consequently, determining the lipid composition of fish is of great significance to evaluate its preservation effect (Meng et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It was obvious that the fishy odorant candidates, for example, 1‐octen‐3‐ol, hexanal, non‐(2 E )‐enal, and ( E , E )‐2,4‐decadienal, disappeared after the fermentation. Subsequently, OAVs were analyzed by dividing the contents with related thresholds according to literatures (Anupam et al., 2010; Chen et al., 2016; Guo et al., 2019; Jia et al., 2019; Liu et al., 2019; Lu et al., 2019; Marsil & Laskonis, 2014; Mu et al., 2017; Narbona et al., 2010; Qian & Wang, 2005; Van Gemert, 2011). In the untreated B .…”
Section: Resultsmentioning
confidence: 99%
“…In order to elucidate whether changes of fishy odorant candidates were responsible to the decreased fishy note or not, potential contributors of fishy note, for example, 1-octen-3-ol, hexanal, non-(2E)-enal, (E,E)-2,4-decadienal, 3,5-octadien-2-one, and 2-pentyl-furan, were quantitatively analyzed using their standards curves correspondingly. As shown in et al, 2010;Chen et al, 2016;Guo et al, 2019;Jia et al, 2019;Liu et al, 2019;Lu et al, 2019;Marsil & Laskonis, 2014;Mu et al, 2017;Narbona et al, 2010;Qian & Wang, 2005;Van Gemert, 2011). In the untreated B. fusco-purpurea, OAVs of 1-octen-3-ol, non-(2E)-enal, (E,E)-2,4-decadienal, 2-pentyl-furan, 2-octen-1-ol, and nonanal were 4,693, 1,275, 1,000, 3,376, 1,928, and 7,045, respectively (Table 3).…”
Section: Oav Analysis Of Fishy Odorants Of B Fuscopurpurea After the Fermentation With The Commercial Starter Culture Of S Cerevisiaementioning
confidence: 94%
“…It has been reported that dietary plant protein and oil sources significantly reduce the contents of the volatiles and improve the nutritional value in fillets of gilthead sea bream [ 5 ]. Low level of dietary fish meal (25%) changes the volatile profiles in cooked fillets of farmed large yellow croaker [ 6 ]. The dietary lipid sources (fish oil and krill oil) help to produce more pleasant flavors by increasing the relative levels of 3-methylbutanal, heptanal, benzaldehyde and nonanal in crab muscle, and the diets with marine oil elevate polyunsaturated fatty acids in muscle [ 7 ].…”
Section: Introductionmentioning
confidence: 99%